Earthquake Disaster Mitigation Mapping By Modeling of Land Layer and Site Effect Zone in The Kota Baru of South Lampung - Haerudin, Nandi; Rustadi, Rustadi; Fitriawan, Helmy; Siska, Deassy; Farid, Muchammad (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2019)
Kota Baru is the satellite city of Bandar Lampung. The city is prepared for the expansion of the city of Bandar Lampung. Zonation map of earthquake risk is required for Kota Baru due to its location within the reach of earthquake energy of Semangko subduction fault. In this study, we model the earthquake-prone zone map based on the soil characteristics (site effect) combined with the underground layer model to get a detailed description of the horizontal and vertical soil character. The microtremor method is performed to obtain the zonation effect mapping. Whereas, the ground layer modeling is obtained using the geoelectrical method. The modeling results show that the study area is far from tectonic activity based on the history of past earthquake events. However, this area has a large sediment thickness and has a low dominant frequency value, so it is an area that is vulnerable to earthquakes.